2t-6=3t+21

Simple and best practice solution for 2t-6=3t+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2t-6=3t+21 equation:


Simplifying
2t + -6 = 3t + 21
Reorder the terms:
-6 + 2t = 3t + 21
Reorder the terms:
-6 + 2t = 21 + 3t
Solving
-6 + 2t = 21 + 3t
Solving for variable 't'.
Move all terms containing t to the left, all other terms to the right.
Add '-3t' to each side of the equation.
-6 + 2t + -3t = 21 + 3t + -3t
Combine like terms: 2t + -3t = -1t
-6 + -1t = 21 + 3t + -3t
Combine like terms: 3t + -3t = 0
-6 + -1t = 21 + 0
-6 + -1t = 21
Add '6' to each side of the equation.
-6 + 6 + -1t = 21 + 6
Combine like terms: -6 + 6 = 0
0 + -1t = 21 + 6
-1t = 21 + 6
Combine like terms: 21 + 6 = 27
-1t = 27
Divide each side by '-1'.
t = -27
Simplifying
t = -27

You can always share this solution

See similar equations:

| 6(8-x)=90 | | -3(3-3r)+7(3r+7)=-20 | | 17.3+v=22.32 | | 3+5x(7-2)=16+5x | | 1.8x=40.14 | | 5(m-1)+m=72 | | (5-6x)/3 | | 6x+4+52= | | 63x^2+74x-9=0 | | x+3-2x=15+x | | -16f=-15f+18 | | 7x+12-9x=16-19x+17x-4 | | (x-6)-(x+2)=5x | | 4x+1=100-7x | | 25x-9-14x+3=24x-3-13x+15 | | -14u=-15u-18 | | 6x+5=7(x-6) | | 4(y+4)=5y+16 | | 1x+21=3 | | A-4/11=2 | | 1=2x+2x-7 | | 4x^2-5x-3=2x^2-3x | | 6y^4-36y^3+54y^2=0 | | 8t^2+44t+48=0 | | 6(5-w)=26 | | 19r=90 | | 9+4x+4x=9 | | -12+3n=-(2n+7) | | 2500x-15000=5000(12-x)^1/2 | | 6(5-w)=35 | | 2(-6x-4)-2(-3x+6)=-26 | | f(x)=l-x+3I | | 6x+12-3x=36 | | 2.4y=4.66y+5.236 | | 6x-10x=-20-12 | | f(x)=l-x+3 | | 112.5/125 | | 2(x-1)+4x=2(-1)+2 | | -14=8n | | 55=X/5 | | x+7y=343 | | 2(b-3)-3=3(b-6) | | 6n^2-4n-10=0 | | -4(6+2x)=-32 | | 78=21/x=8/× | | 2/3=5(y-0.2 | | 38-14=41-x | | y=3x(x-3) | | 2x-20+3x+10=180 | | y=5(6.33-1.67y)-13 | | 9p=10p+9 | | 4v+2=9v+6-v | | 10u^7+26u^6-12u^5=0 | | -t-10=-6t+10 | | N=(-5/-3)(4/2) | | 8+8d=-6+6d | | -13+3x=11+x | | k=2k-5 | | (5/0)(25/12) | | -2x-7=6x-63 | | 5/14•C=1/2 | | 2-2m=-3m+10 | | 6c-4-C=24 | | 0=3x(x-3) | | -5c=8-3c |


Related pages


170-174izprime factorization 5625000 dollars in poundsroman numerals 100000calculator quadratic equation2x 5y 7prime factorization for 4424.99 to dollarsgcf of 105square root 441the lcm of 3 and 435 prime factorizationx2 3x 7 0what is a prime factorization of 42derivative sin4x212-32roman numerals 1-1000000graph sinxgreatest common monomial factor calculatory 2cosxderivative of ln x 2 1prime factors of 1225800-6224x 5yprime factorization 2254x 12x2cos2x-1 0derivative of tan 5 xfactorization calculatorhow to write 0.4 as a fraction729.56yigcf of 63 and 10860x33aw website82-668.314prime factorization of 2205prime factorization for 196y7 ywhat is 0.11111 as a fractionwhat is 0.125 as a percentpv nrt equationsolve 3x 1 5gcf generatorderivative of x cos xgraph sin 4xsolve the equation by making an appropriate substitutiony 6xcommon multiples of 4 and 83.14 r squaredpqrstugraph 2x 3y 18factors of 68594x 1 3x 14y x 1derivative of ln139.99 x 12greatest common factor of 120what is the prime factorization of 104hrtv112abcroads advancedacademicshcf of 72 and 96greatest common factor of 120x3 2x2sinx cos xfactor x2 6x 91972 roman numeralswhat is the prime factorization of 101derivative of ln 7xexpand 2x 2y 54x 2y 8 03r solutions